Técnicas multivariadas para detecção das respostas auditivas em regime permanente - Tiago Zanotelli (2011)
Auditory Steady-State Response (ASSR) is a potential elicited in the brain due to stimulation rapid stimulation enough that the response to a given stimulus overlaps the response the next stimulus. Detection of ASSR has been used to estimate a physiological audiometric, especially in individuals who do not respond to conventional tonal exam. Multivariate techniques of Objective Response Detection (ORD) which use energy information (F Spectral Test), phase (Component Synchrony Measure CSM) and coherence (Magnitude Square Coherence MSC) have been used to identify ASSR. One of the problems of the ASSR exam is its duration, which varies from 45 to 60 minutes. The present dissertation aims to investigate the use of Multivariate ORD (MORD) to detect ASSR with AM tones, to reduce detection time. The MORD techniques used were: Multiple Component Synchrony Measure (MCSM) and Multiple Magnitude Squared Coherence (MMSC). The EEG signals were collected from eight (8) healthy volunteers in F3, F4, Fz, C3, C4, Cz, P3, P4, Pz, T3, T4 and Oz during two sessions of 16 minutes stimulation with intensities of 60 and 40 dB SPL. In each session, a stimulus was presented simultaneously on the left and right ears composed of 4 AM tones carriers of 0.5, 1, 2 and 4 kHz for both ears and modulated, respectively, at 78, 83, 88 and 92 Hz for the right ear and 81, 85, 90 and 95 Hz for the left. Results showed that the use of MORD techniques with 5 channels can reduce ASSR detection time in up to 25.15% (MMSC) compared to the ORD techniques (MSC). Thus, MORD techniques were seen as a promising tool, for ASSR detection, and can be used to reduce acquirement times for physiological auditory threshold.